THE INTERNATIONAL INVESTMENT AGREEMENT NOWADAYS: FROM THE CONSENT TO ITS SOCIAL FUNCTION AS A GUARANTOR OF THE INTERESTS OF CITIZENS - Gaspar, Renata Alvares; Castro, Felipe Soares Vivas de (PANORAMA OF BRAZILIAN LAW, 2018)
At the center of a globalized world and under intense transnational financial circulation, there is the foreign investment. In this sense, investigating the realization of the social and economic functions of the Foreign Investment Agreement is an insurmountable necessity for understanding its effects on the citizenship rights. Therefore, it was discussed the rapid and multiple transformations that the International Investment Law has been supporting over time and the direct reflection on the formation of the Foreign Investment Contracts that, nowadays, require complex answers to the achievement of legal security.